What Drives Entrepreneurial Intention in the Digital Era? Insights from Postgraduate Students Experiencing AI-Based Entrepreneurial Education - Sri Yusriani; Haniruzila Hanifah; Endi Rekarti; Shine Pintor Siolemba Patiro; Muji Gunarto (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
Entrepreneurial intention (EI) has become a central focus in understanding how students transform learning experiences into entrepreneurial behavior, particularly amid the transition from the Fourth to the emerging Fifth Industrial Revolution. This preliminary study explores the determinants of perceived EI among postgraduate students in Indonesia, emphasizing the mediating role of Entrepreneurial Education on Artificial Intelligence (EEOAIN) as an integral component of the curriculum designed to prepare students for business start-up initiatives. A qualitative approach was employed using semi-structured, one-on-one interviews with eight postgraduate students representing various provinces and disciplines, including management, computer science, and education. The discussions aimed to uncover factors that strengthen entrepreneurial intention and to explore how individual psychological traits: Self-Efficacy (SE), Leadership Skills (LS), Digital Skills (DS), Work Experience (WE), and Perceived Stress (PST), influence EI within the rapidly evolving digital learning ecosystem. The findings reveal that EEOAIN is perceived as a transformative driver that enhances students’ readiness for entrepreneurial activity through exposure to AI-based innovations. Perceived University Support (PUS) and Positive Emotions (POEM) are identified as moderating factors that reinforce entrepreneurial intentions, thereby fostering entrepreneurial development and expanding employment opportunities for Indonesians. PUS acts as an external enabler by providing mentoring, resources, and social capital, while POEM functions as an internal psychological catalyst that promotes resilience and creativity. Collectively, these preliminary insights validate the conceptual model and provide empirical grounding for future quantitative investigations. This study offers initial evidence supporting the integration of technological, institutional, and emotional dimensions in shaping entrepreneurial intentions within higher education in developing-country contexts.